Meningkatkan Kemampuan Berpikir Kritis dalam Pak dengan Metode Problem Based Learning Fase C Kelas VI SD Suster Pontianak - Saparini Saparini; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
The problem faced by Grade VI B students is their low critical thinking skills and academic achievement. The teacher has not yet applied student-centered learning methods. So far, the learning approach used has been dominated by lectures. This study aims to: 1) improve students' critical thinking skills, and 2) improve students' learning outcomes. This classroom action research was conducted in four stages: planning, implementation, evaluation, and reflection, involving 31 Grade VI B students as research subjects. The study was carried out in two cycles using the Problem-Based Learning (PBL) approach. Data analysis was conducted using descriptive percentage methods. The focus on the Critical Reasoning dimension of the Pancasila Student Profile aims to enhance the affective aspect of learning. The results showed an improvement in the affective aspect of students' critical thinking skills by 6%, from 82% in cycle I to 88% in cycle II. Meanwhile, the cognitive test results showed an increase in learning mastery from 90% in cycle I to 100% in cycle II. The reflection results recommend the need for assistance in developing students' affective aspects to further enhance their critical thinking skills and learning outcomes. In conclusion, the application of Problem-Based Learning (PBL) focusing on the Critical Reasoning dimension of the Pancasila Student Profile can improve students' learning outcomes.